First-principles study on the NMR shielding of transition metal semiconductors. (1st June 2023) - Xu, Chen; Xiang, Yunfei; Shi, Chenglong
Abstract: The theoretical calculation of chemical shielding can help us understand the information of nuclear magnetic resonance experiment more deeply. In this work, three different functionals had been used to study the isotropic shielding of various transition metal nuclei. The predicted trend of our theoretical results matched the experimental results well. It was found that the large (more than 2000 ppm) variation of measured 93 Nb and 51 V chemical shifts were mainly determined by the occupied and empty states of d orbitals. Furthermore, the effect of the energy differences between the occupied and empty states of d orbitals had been discussed as well. This work is helpful to understand the sources and differences of chemical shifts of certain nuclei in transition metal semiconductors. Highlights: The solid-state chemical shifts of transition metal nuclei have been systematically calculated. Both occupied and empty states of d orbital contribute to the chemical shielding. The energy difference of occupied and empty states contributes to chemical shielding.